The Health of Older People in Switzerland - P Chastonay; D Weber; T Mattig (Journal of Public Health International, 2018)
Over the past century, the proportion of Swiss residents aged 65 or older rose from 5.8% to 17.8%; during the same period, the proportion aged over 80 rose from 0.5% to 5.0%. Although the majority of older people in Switzerland enjoy good health, disease prevalence rises with age. Almost half (49%) of people over 65 living at home report at least one chronic illness. Among the 65- to 79-year-olds living at home, 25.2% suffer from several chronic diseases; among people in the 80s, this figure reaches 41.3%. People aged over 80 are also particularly at risk for falls (30%). In addition, between 15% and 25% of the elderly suffer from at least one mental illness. Close to 30% of healthcare costs are attributable to people over the age of 75, who make up only 8% of the total population. Given the public health importance of the issue a health promotion project targeting the elderly – the VIA Project -, based on successful local programs, is being implemented throughout the country. The overall goal of the VIA project is to promote the health of older people and to strengthen their self-determination and independence.
Keywords: Health of the elderly